Common variable immunodeficiency—an independent risk factor for atherosclerotic cardiovascular diseases - Mattila, Juho; Pitkänen, Niina; Järveläinen, Hannu (Frontiers in Cardiovascular Medicine, 2023)
Atherosclerosis, a disease of chronic inflammation of the arterial wall, is the main cause of most cardiovascular diseases (CVDs). Common variable immunodeficiency (CVID), a group of diseases characterized by frequent infections due to defective antibody production and lack of human immunoglobulins, plays a role in immune activation and inflammation. Thus, it can be hypothesized that CVID increases the risk for atherosclerotic CVDs. On the other hand, it is also possible that CVID patients are protected from atherosclerotic CVDs based on their lifelong immunoglobulin therapy.Here, we examined whether patients with CVID have an increased risk for atherosclerotic CVDs or whether they are protected from these diseases. Using an electronic patient database registry search of a population of 83 CVID patients and their age-and sex-matched, tenfold larger control population we demonstrate that CVID patients have a statistically significantly higher risk for coronary heart disease (OR 2.4, p=0.015) and peripheral vascular disease (OR 12.5, p<0.001). Regarding cerebrovascular disease, there was a trend towards CVID patients having more strokes or ischemic attacks, but the difference was not statistically significant (OR 2.0, p=0.133). The combined OR for CVID patients for atherosclerotic CVDs was 2.6 (p=0.001). CVID population had more hypertension, but smoking was more seldom. There were no statistically significant differences in the incidence of diabetes or levels of serum total, HDL or LDL cholesterol, or glycosylated hemoglobin A1c between CVID patients and their controls. CVID patients had infections more frequently and the OR for autoimmune diseases was 3.8 (p<0.001). Finally, a multivariate logistic analysis showed that CVID is an independent risk factor for atherosclerotic CVDs (p=0.002).